👤

Learning Task 1: Solve the following equation​

Learning Task 1 Solve The Following Equation class=

Sagot :

Solving for x in Radical Equations

In solving for x in a radical equation, first, remove the radical sign by raising both sides of the equation with the given index. Simplify. Next, if x has a numerical coefficient, divide both sides of the equation with the numerical coefficient of x. Again simplify. Check if the equation is balanced.

Learning Task 1:

Answers:

  1. x = 81
  2. x = 72
  3. x = [tex]\frac{9}{4}[/tex]
  4. x = 25
  5. x = 27
  6. x = 9
  7. x = 32
  8. x = 189
  9. x = 1
  10. x = 64
  11. x = 8
  12. x = ±12
  13. x = 3, x = -1
  14. x = -1/4, x = 1
  15. x = 0

Solutions:

1. [tex]\sqrt{x}[/tex] = 9                        2. [tex]\sqrt[3]{3x}[/tex] = 6                         3. 4[tex]\sqrt{x}[/tex] = 6

  ([tex]\sqrt{x}[/tex])² = 9²                        ([tex]\sqrt[3]{3x}[/tex])³ = 6³                        4²([tex]\sqrt{x}[/tex])² = 6²

  x = 81                               3x = 216                            16x = 36

                                           [tex]\frac{3x}{3}[/tex] = [tex]\frac{216}{3}[/tex]                              [tex]\frac{16x}{16}[/tex] = [tex]\frac{36}{16}[/tex]

                                           x = 72                                x = [tex]\frac{9}{4}[/tex]

4. 7 + [tex]\sqrt{x}[/tex] = 12               5.  [tex]\sqrt[4]{3x}[/tex] - 5 = -8                  6.  [tex]\sqrt{3x - 2}[/tex] = 5

   7 - 7 + [tex]\sqrt{x}[/tex] = 12 - 7          [tex]\sqrt[4]{3x}[/tex] - 5 + 5 = -8 + 5           ([tex]\sqrt{3x - 2}[/tex])² = 5²

  [tex]\sqrt{x}[/tex] = 5                             [tex]\sqrt[4]{3x}[/tex] = -3                             3x - 2 = 25

 ([tex]\sqrt{x}[/tex])² = 5²                         ([tex]\sqrt[4]{3x}[/tex])⁴ = -3⁴                        3x - 2 + 2 = 25 + 2

 x = 25                               3x = 81                               3x = 27

                                           [tex]\frac{3x}{3}[/tex] = [tex]\frac{81}{3}[/tex]                                [tex]\frac{3x}{3}[/tex] = [tex]\frac{27}{3}[/tex]

                                            x = 27                               x = 9

7. [tex]\sqrt[5]{x}[/tex] + 5 = 7                 8.  [tex]\sqrt[3]{x}[/tex] = 3[tex]\sqrt[3]{7}[/tex]                      9. 8 - [tex]\sqrt[4]{x}[/tex]  = 7

   [tex]\sqrt[5]{x}[/tex] + 5 - 5 = 7 - 5           ([tex]\sqrt[3]{x}[/tex])³ = 3³([tex]\sqrt[3]{7}[/tex])³                  8 - 8 - [tex]\sqrt[4]{x}[/tex] = 7 - 8

   [tex]\sqrt[5]{x}[/tex] = 2                             x = 27(7)                           -[tex]\sqrt[4]{x}[/tex] = -1

   ([tex]\sqrt[5]{x}[/tex])⁵ = 2⁵                        x = 189                              (-[tex]\sqrt[4]{x}[/tex])⁴ = -1⁴

   x = 32                                                                        x = 1

10. 3[tex]\sqrt[3]{x}[/tex] = 12              11. [tex]\sqrt{2x + 2}[/tex] =  [tex]\sqrt{x + 10}[/tex]           12.  [tex]\sqrt{x^2 - 144}[/tex] = 0

     3³([tex]\sqrt[3]{x}[/tex])³ = 12³            ([tex]\sqrt{2x + 2}[/tex])² = ([tex]\sqrt{x + 10}[/tex] )²          ( [tex]\sqrt{x^2 - 144}[/tex])² = 0²

     27x = 1728               2x + 2 = x + 10                        x² - 144 = 0

     [tex]\frac{27x}{27}[/tex] = [tex]\frac{1728}{27}[/tex]                   2x - x = 10 - 2                         x² = 144

     x = 64                       x = 8                                       x = [tex]\sqrt{144}[/tex]

                                                                                      x = ±12

13. x + [tex]\sqrt{x^2 + 3}[/tex] = 3x                           14. 2[tex]\sqrt{3x + 1}[/tex] = 4x

     x - 3x + [tex]\sqrt{x^2 + 3}[/tex] = 3x - 3x                 2² ([tex]\sqrt{3x + 1}[/tex])² = (4x)²

     -2x + ([tex]\sqrt{x^2 + 3}[/tex])² = 0                          4(3x + 1) = 16x²

     -2x + x² + 3 = 0                                 12x + 4 = 16x²

     x² - 2x + 3 = 0                                   -16x² + 12x + 4 = 0

    (x - 3)(x + 1) = 0                                   -1[-16x² + 12x + 4 = 0]

    x = 3, x = -1                                           16x² - 12x - 4 = 0

                                                                 (8x + 2)(2x - 2) = 0

                                                                 x = -1/4, x = 1

15. 2 + [tex]\sqrt{x + 1}[/tex] - [tex]\sqrt{x - 5}[/tex] = 0

     2² + ([tex]\sqrt{x + 1}[/tex])² - ([tex]\sqrt{x - 5}[/tex])² = 0²

     4 + x + 1 - x + 5 = 0

     0x = -10

     x = 0

How to find for x in a radical equations: https://brainly.ph/question/11045142

#BrainlyEveryday